The Nonparadigmaticly Formed Adjectives and Their Status in Word-forming Paradigm - Mitter, Patrik (Bohemica Olomucensia, 2017)
Study deals with the nonparadigmaticly formed adjectives in word-forming paradigms of czech verbs. Verbs are suitable material for studying word-forming paradigms because of their large derivation potenciality (especially prefixal derivation is potencial) and for their ability to form verbal aspectual counterparts and multiplicativity counterparts. Study is focused on verbal ability to be basis of nonparadigmatical formation of verbal adjectives. Study indicates how is possible to record these adjectives in word-forming paradigma.
Keywords: adjectiv; word-forming; morphology; derivation; paradigms